ILMU DAN ORANG BERILMU DALAM AL-QURâ€™AN: MAKNA ETIMOLOGIS, KLASIFIKASI, DAN TAFSIRNYA - Surahman Amin dan Ferry Muhammad Siregar (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2015)
This paper aims at discussing about knowledge (â€˜al-â€˜ilm) and scholar (al-â€˜Älim) in the Qurâ€™an with a focus onÂ their etymological meanings, classification and interpretation (tafsÄ«r). In addition, it examines the words ofÂ verses related to al-â€˜ilm and al-Älim, being analyzed by the theory of Qurâ€™anic exegesis, especially tafsÄ«r mauá¸Å«â€™Ä«.Â It faund that the al-â€˜ilm is a real knowledge on an object in accordance with its conditions and characters. Al-Â â€™ilm can be divided into two types, i.e. kasbÄ« (gained knowledge) and ladunnÄ« or mawhibah (gifted knowledge).Keywords: Knowledge, TafsÄ«r, â€˜UlamÄâ€™